1995
DOI: 10.1007/bf00230042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reversible dorsal cold block on the persistence of inhibition generated by spinal reflexes

Abstract: The effects of bilateral focal cooling of dorsolateral thoracic spinal cord on segmental reflex pathways to the triceps surae muscles were assessed in decerebrate cats from the reflex forces produced by single shocks or trains of electrical stimuli applied to the ipsilateral caudal cutaneous sural and the contralateral tibial nerves. The validity of the dorsal cold block technique as a substitute for acute surgical dorsal hemisection was established by showing that focal cooling reliably reproduced the stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…It was suggested that PLRs in intact animals contribute substantially to postural reactions (Musienko et al, , 2010Deliagina et al, 2012). We have found that the spinal cord contains neuronal networks capable of generating PLRs in response to postural perturbations (Musienko et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…It was suggested that PLRs in intact animals contribute substantially to postural reactions (Musienko et al, , 2010Deliagina et al, 2012). We have found that the spinal cord contains neuronal networks capable of generating PLRs in response to postural perturbations (Musienko et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…During the experiment, the rectal temperature and mean blood pressure of the animal were continuously monitored and were kept at 37-38°C and at Ͼ90 mmHg, respectively. Recordings were started not Ͻ1 h after cessation of anesthesia, when the functional state of the preparation could be characterized by rather stable extensor tonus and pronounced PLRs (see below), which are important attributes of postural activity (Musienko et al, , 2010.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations